Reproductive performance and disorders in mares - Purohit, G N; Sharma, B S; Gupta, K A (The Indian Journal of Animal Sciences, 2012)
Reproductive performance and disorders were studied for thoroughbred mares from 1993 to 1996. The overall mean estrus cycle length (EL) and estrus period (EP) were 14.98Â±1.12 and 6.04Â±0.248 days. Both EL and EP did not vary between the years, but differed significantly between the months (P